Differential urinary specific gravity as a molecular phenotype of the bladder cancer genetic association in the urea transporter gene, SLC14A1. Issue 12 (16th July 2013) - Koutros, Stella; Baris, Dalsu; Fischer, Alexander; Tang, Wei; Garcia‐Closas, Montserrat; Karagas, Margaret R.; Schwenn, Molly; Johnson, Alison; Figueroa, Jonine; Waddell, Richard; Prokunina‐Olsson, Ludmila; Rothman, Nathaniel; et al.
<x xml:space="preserve">Abstract</x> Genome‐wide association studies (GWAS) identified associations between markers within the solute carrier family 14 (urea transporter), member 1 (SLC14A1) gene and risk of bladder cancer. SLC14A1 defines the Kidd blood groups in erythrocytes and is also involved in concentration of the urine in the kidney. We evaluated the association between a representative genetic variant (rs10775480) of SLC14A1 and urine concentration, as measured by urinary specific gravity (USG), in a subset of 275 population‐based controls enrolled in the New England Bladder Cancer Study. Overnight urine samples were collected, and USG was measured using refractometry. Analysis of covariance was used to estimate adjusted least square means for USG in relation to rs10775480. We also examined the mRNA expression of both urea transporters, SLC14A1 and SLC14A2, in a panel of human tissues. USG was decreased with each copy of the rs10775480 risk T allele (p‐trend = 0.011) with a significant difference observed for CC vs. TT genotypes (p‐valuetukey = 0.024). RNA‐sequencing in the bladder tissue showed high expression of SLC14A1 and the absence of SLC14A2, while both transporters were expressed in the kidney. We suggest that the molecular phenotype of this GWAS finding is the genotype‐specific biological activity of SLC14A1 in the bladder tissue. Our data suggest that SLC14A1 could be a unique urea transporter in the bladder that has the ability to influence urine concentration and that this mechanism might explain the increased bladder cancer susceptibility associated with rs10775480.